Gambaran IMT pada Mahasiswa Tingkat 1 Politeknik Negeri Indramayu: Overview Of Body Mass Index (BMI) First Grade Nursing Student - Sulastri, Indah; Laras Sati, Naela; Khosyatillah, Naila; Rukmana, Muhammad Iqbal; Rochma, Widya Nur; Nurjanah, Suci (Program Studi Keperawatan Waikabubak, Politeknik Kesehatan Kementerian Kesehatan Kupang, 2024)
Introduction: Body mass index (BMI) is a standard for classifying body composition. A perfect body is the desire of both men and women. Delays in nutritional intake will have an indirect impact on Body Mass Index (BMI). There are several factors to determine BMI and also those that can influence it, including diet, type of food, and level of physical activity. A perfect body is everyone's desire, both women and men. The ideal body can be calculated using the Body Mass Index (BMI), which is a measurement standard based on the relationship between height and weight, so that it can be categorized as normal, deficient, overweight or obese. The order of BMI value categories is underweight, normal, overweight and obese. Low knowledge about balanced nutrition is one of the causes of changes in eating patterns. With a lack of understanding of nutrition, students' efforts to determine healthy foods are also reduced. Objective: The aim of this research is to calculate the nutritional status of students by calculating Body Mass Index. Method: This research uses analytical descriptive research using data collection by distributing questionnaires. Results: The results obtained by the frequency distribution of nutritional status measurements of the highest respondents were normal 26 people (86.7%), Overweight 3 people (10%), and Underweight 1 person (3.3%). This shows that BMI respondents have a normal or ideal body weight